TREMATODOS DE LOS MURCIELAGOS DE MEXICO IV DESCRIPCION DE UN NUEVO GENERO DE LA SUBFAMILIA LECITHODENDRIINAE LOOSS 1902 Y UNA NUEVA ESAN LUIS POTOSIECIE DE PROSTHODENDRIUM DOLLFUS 1931 - CABALLERO Y C, EDUARDO (Universidad Nacional Autónoma de Mexico, CD MEXICO, DF, MEX, 1943)
The author found in the large intestine of 2 turtles the following Trematodes: Choanophorus rovirosai, Octangioides tlacotalpensis, Dermatemytrema trifoliata, and PARACHIORCHIS parviacetabulatus
ANS INST BIOL
Keywords: TREMATODOS, MURCIELAGOS, MEXICO, DESCRIPCION, NUEVO GENERO, SUBFAMILIA, LECITHODENDRIINAE LOOSS, 1902, NUEVA ESPECIE, PROSTHODENDRIUM DOLLFUS, 1931; CIENCIAS DE LA VIDA; BIOLOGIA ANIMAL; MAMIFEROS